Wiley's English-Spanish Spanish-English chemistry dictionary - Kaplan, Steven M. (Hoboken, New Jersey : Wiley, 2013)
This Dictionary provides over 75,000 entries covering all areas of chemistry, such as Chemical Biology, Biochemistry, Biotechnology, and Nanochemistry, plus relevant terms in related spheres of expertise. In order to prepare this Second Edition, the First Edition was completely revised, and over 35,000 new terms were added. This new edition will continue to be the Dictionary that chemists, educators, students, translators, and those working in English and Spanish in chemistry and associated fields have been trusting since the First Edition was published in 1998.
Includes index.
Print version record and CIP data provided by publisher.
Keywords: Chemistry -- Dictionaries; English language -- Dictionaries -- Spanish; Chemistry -- Dictionaries -- Spanish; Spanish language -- Dictionaries -- English; SCIENCE -- Chemistry -- General; Chemistry; English language; Spanish language; Electronic books; Dictionaries